Ein Vergleich der Ergebnisse der ersten Welle des Österreichischen Survey of Health, Ageing and Retirement in Europe (SHARE) und der Österreichischen Gesundheitsbefragung (ATHIS) - Maike Wendland; Isabella Buber (Austrian Academy of Sciences (ÖAW), Vienna Institute of Demography (VID), 2009)
– To anticipate future challenges that arise from the ageing society in Austria, it is necessary to analyse already today the health of elderly people. Currently, two datasets are available for this purpose, namely the Survey of Health, Ageing and Retirement in Europe (SHARE) and the Austrian Health Interview Survey (ATHIS). In a first part, the present study depicts a qualitative comparison of both questionnaires concerning the coverage of the state of health, health behaviour and health care utilisation. In a second, it presents a comparison of descriptive findings for persons aged 50 years and more regarding the prevalence of various chronic diseases. A comparison of the included questions shows that both surveys are in different ways adaptive to the requirements of elderly people. Yet the benefit of SHARE is that it captures the socio-demographic circumstances of elderly people much more broadly than ATHIS. Moreover, SHARE allows a dynamic analysis of the ageing process due to its longitudinal design. The results of descriptive analyses reveal a higher prevalence for most diagnoses of chronic diseases in ATHIS. Certain diseases - like cancer or osteoporosis - tend to be underrepresented in SHARE. In general, the persons interviewed in SHARE tend to be healthier than those included in ATHIS. The higher level of education of the SHARE sample might only partly explain this discrepancy.
Keywords: 300; Austrian health survey; SHARE; ATHIS; comparison of data; ageing; Austria; health; Alternde Bevölkerung; Bevölkerungsstatistik; Datenqualität; Vergleich; Österreich